2022
DOI: 10.2196/37913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Clinical Text–Based Fall Prediction Model on Preventing Extended Hospital Stays for Elderly Inpatients: Model Development and Performance Evaluation

Abstract: Background Falls may cause elderly people to be bedridden, requiring professional intervention; thus, fall prevention is crucial. The use of electronic health records (EHRs) is expected to provide highly accurate risk assessment and length-of-stay data related to falls, which may be used to estimate the costs and benefits of prevention. However, no studies to date have investigated the extent to which hospital stays could be shortened through fall avoidance resulting from the use of prediction tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This study reported that the fall group had a longer length of stay with 11.86 days than the non-fall group with 7.34 days, which was comparable to the result of the previous study that the faller group tended to be with a longer hospital stay [33]. On the other hand, there was a previous study showing a converse relationship that the extended length of hospital stay was due to patient falls [34]. Therefore, we estimated the relative odds and relative hazard in patient falls according to the length of stay in hospital.…”
Section: Discussionsupporting
confidence: 84%
“…This study reported that the fall group had a longer length of stay with 11.86 days than the non-fall group with 7.34 days, which was comparable to the result of the previous study that the faller group tended to be with a longer hospital stay [33]. On the other hand, there was a previous study showing a converse relationship that the extended length of hospital stay was due to patient falls [34]. Therefore, we estimated the relative odds and relative hazard in patient falls according to the length of stay in hospital.…”
Section: Discussionsupporting
confidence: 84%
“…The absence of external validation is another significant limitation, as it is crucial for confirming the efficacy and robustness of our models. Finally, the dependency of radiomics and deep learning models on imaging quality means that variations in (46)(47)(48). Therefore, due to the small sample size in our study, we did not adopt this model methodology.…”
Section: Discussionmentioning
confidence: 99%
“…LLMs are powerful and can be used for fall detection. Current literature has explored other tools that have identified fall events within controlled settings with very high sensitivities and specificities 12,13 . However, these approaches have largely been institution-specific and have relied on large annotated datasets which are cumbersome to produce.…”
Section: Discussionmentioning
confidence: 99%
“…Their approach examined how to balance false positives and false negatives with multiple models. Kawazoe et al (2022) 12 developed an approach using structured data and BERT to classify clinical notes written in Japanese to detect and predict falls. Their approach had good sensitivity (0.74) and specificity (0.84) but low PPV (0.09).…”
Section: Discussionmentioning
confidence: 99%